Identifikasi Mutu Bubur Instan Berbasis Tepung Pisang Jantan (Musa Acuminata Colla) Dan Tepung Ikan Selengek (Anondontostoma Chacunda) - Hesti Nur'aini; Febry Dian Saputra; Darius Darius (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
Instant porridge is made from raw materials such as rice, cereals, or other food ingredients, through a special processing process so that it can be consumed quickly and easily. This processing process generally involves stages such as grinding, pre-cooking, drying, and the addition of other ingredients to improve nutritional value or taste. The purpose of this study was to characterize the effect of the addition of banana flour and longan fish flour on the characteristics of instant porridge. This study used a factorial design consisting of one factor with six levels of composition treatment, namely without the addition of banana and fish, 15 g of banana flour + 0 grams of longan fish flour, 12 grams of banana flour + 3 grams of longan fish flour, 9 grams of banana flour + 6 grams of longan fish flour, 6 grams of banana flour + 9 grams of longan fish flour, and 3 grams of banana flour + 12 grams of longan fish flour. Analysis carried out on instant porridge consisted of analysis of yield, water content, protein content, fiber content, fat content, organoleptic test, and business feasibility analysis. Processing instant porridge with the addition of banana flour and longan fish flour produces instant porridge with a yield of between 89.83% - 81.67%, water content between 2.24% - 7.84%, protein content of 3.38% - 11.92%, fiber content of 10.73% - 6.54%, and fat content of 8.00% - 12.41%. The best treatment is found in instant porridge with the addition of 6 g of banana flour and 9 g of longan fish flour, with a value of 1.57 and an effectiveness value of 2.65. The R/C value of the instant porridge business ratio is 1.20.